2022
DOI: 10.3390/bioengineering10010004
|View full text |Cite
|
Sign up to set email alerts
|

Towards a New Concept of Regenerative Endodontics Based on Mesenchymal Stem Cell-Derived Secretomes Products

Abstract: The teeth, made up of hard and soft tissues, represent complex functioning structures of the oral cavity, which are frequently affected by processes that cause structural damage that can lead to their loss. Currently, replacement therapy such as endodontics or implants, restore structural defects but do not perform any biological function, such as restoring blood and nerve supplies. In the search for alternatives to regenerate the dental pulp, two alternative regenerative endodontic procedures (REP) have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 163 publications
0
9
0
Order By: Relevance
“…Sci. 2023, 24, x FOR PEER REVIEW 8 of 15 [108,109]. The various steps of centrifugation are required to remove these apoptotic bodies.…”
Section: Secretome-derived Product Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sci. 2023, 24, x FOR PEER REVIEW 8 of 15 [108,109]. The various steps of centrifugation are required to remove these apoptotic bodies.…”
Section: Secretome-derived Product Purificationmentioning
confidence: 99%
“…These elements include proteins and extracellular vesicles. These extracellular vesicles can contain apoptotic bodies, which appear during the programmed cell death process [ 108 , 109 ]. The various steps of centrifugation are required to remove these apoptotic bodies.…”
Section: Secretome-derived Product Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown similarities between DPSCs and bone marrow stromal cells, which improve the application of DPSCs in musculoskeletal regenerative medicine [15]. These cells are also targeted in research as a source of autologous cells, which are of great interest in the field of regenerative medicine, both inside and outside the oral cavity [18]. Table 1 summarizes the key properties of DPSCs.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the proposal for a cell-free approach to dental pulp regeneration using MSC-derived CM/EV: (A) The treatment sequence for immature permanent teeth with pulp necrosis is outlined; (B) The regenerative procedure for cases with partially damaged pulp is summarized. Key components involved include: MTA (mineral trioxide aggregate), SCAP (stem cells from apical papilla), EDTA (ethylenediaminetetraacetic acid)[53].…”
mentioning
confidence: 99%